Biodegradation of polyethylene using Pseudomonas sp.: developing sustainable processes for a circular economy - Nixon, Morag (2025)
While synthetic polymers are valuable and versatile, their durability has led to an increasing disposal challenge. Current routes for plastic waste are limited to landfill, incineration and mechanical recycling. Biological recycling utilises microorganisms and enzymes to degrade plastic, producing sustainable chemical products. This project focuses specifically on polyethylene (PE), due to the significant contribution (~26 %) PE makes to the global plastic market. Additionally, polyolefin degradation is less understood compared to other plastic degradation.